2015
DOI: 10.1371/journal.pone.0122384
|View full text |Cite
|
Sign up to set email alerts
|

Hunting for the LCT-13910*T Allele between the Middle Neolithic and the Middle Ages Suggests Its Absence in Dairying LBK People Entering the Kuyavia Region in the 8th Millennium BP

Abstract: Populations from two medieval sites in Central Poland, Stary Brześć Kujawski-4 (SBK-4) and Gruczno, represented high level of lactase persistence (LP) as followed by the LCT-13910*T allele’s presence (0.86 and 0.82, respectively). It was twice as high as in contemporaneous Cedynia (0.4) and Śródka (0.43), both located outside the region, higher than in modern inhabitants of Poland (0.51) and almost as high as in modern Swedish population (0.9). In an attempt to explain the observed differences its frequency ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 71 publications
1
7
0
2
Order By: Relevance
“…It was reported that LCT-13910 CT and TT genotypes associated with LT were subjected in Europe to a strong positive selection for over 3000 years. The TT and CT genotypes were absent in early Neolithic Farmer populations and present in only 10% of Bronze Age European people [ 9 , 10 , 11 ]. In Europe the LT has increased from Iron Age through Medieval Period till present day times [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that LCT-13910 CT and TT genotypes associated with LT were subjected in Europe to a strong positive selection for over 3000 years. The TT and CT genotypes were absent in early Neolithic Farmer populations and present in only 10% of Bronze Age European people [ 9 , 10 , 11 ]. In Europe the LT has increased from Iron Age through Medieval Period till present day times [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note, however, that due to recent discoveries of LP prevalence in the European Neolithic (Burger et al 2007;Gamba et al 2014;Witas et al 2015;Olalde et al 2018;Brace et al 2019), it is unlikely that the British Neolithic individuals studied here would have carried the genetic mutation associated with lactase persistence. Human remains from neither Hambledon Hill nor Hazleton North have been subjected to ancient DNA analysis to date, but none of the individuals (n = 3) genetically analysed thus far from Banbury Lane have a derived lactase persistence allele (Brace et al 2019).…”
Section: Resultsmentioning
confidence: 88%
“…Advances in next-generation sequencing technologies and the emergence of full genome characterisation of archaeological samples however now suggest that LP may not have been prevalent in the Neolithic, but instead present only in very low frequencies across the population, if present at all. The absence of LP in European Neolithic populations has now been noted in a number of studies (e.g., Burger et al 2007;Gamba et al 2014;Witas et al 2015;Olalde et al 2018;Brace et al 2019), and Allentoft et al (2015) suggest that LP had a very low frequency (5-10%) even in Bronze Age European populations, indicating that LP is the result of more recent positive selection. Similarly, a large-scale study by Mathieson et al (2015) suggests that LP in Europe only became under strong selection within the last 4000 years.…”
Section: Lactase Persistence and The Origins Of Milk Consumptionmentioning
confidence: 90%
“…A recent study of 400 Neolithic, Chalcolithic and Bronze Age Europeans (Olalde et al, 2018) observed that the T allele remained at a very low frequency across the transition from the Neolithic period to the Bell Beaker and Bronze Age periods, both in Britain and continental Europe, with a major increase in its frequency occurring only within the last 3500 years (Brace et al, 2018). Table 1 summarizes some such results of Allentoft et al (2015), Mathieson et al (2015), and Olalde et al (2018) based on the Central European chronology in Haak et al (2015); readers may also refer to Witas et al (2015), Liebert et al (2017) and Ségurel and Bon (2017).…”
Section: Introductionmentioning
confidence: 96%